Timing of Intra-Articular Injection of Synovial Mesenchymal Stem Cells Affects Cartilage Restoration in a Partial Thickness Cartilage Defect Model in Rats. (January 2020) - Enomoto, Takahiro; Akagi, Ryuichiro; Ogawa, Yuya; Yamaguchi, Satoshi; Hoshi, Hiroko; Sasaki, Toshihide; Sato, Yusuke; Nakagawa, Ryosuke; Kimura, Seiji; Ohtori, Seiji; Sasho, Takahisa
Objective: We investigated the effect of administration of intra-articular mesenchymal stem cells (MSCs) on cartilage repair at different timings, and the distribution of MSCs in the knee. Design: A partial thickness cartilage defect (PTCD) was created on the medial femoral condyle in 14-week-old Sprague-Dawley rats. Intra-articular injection of 1 × 10 6 MSCs was performed at 3 time points, namely at the time of surgery (0w group), at 1 week after surgery (1w group), and at 2 weeks after surgery (2w group). For the control, 50 μL phosphate-buffered saline was injected at the time of surgery. The femoral condyles were collected at 6 weeks after creation of PTCD and assessed histologically. To investigate the distribution of MSCs, fluorescent-labeled MSCs were injected into the knee joint. Results: In the control group, the cartilage lesion was distinguishable from surrounding cartilage. In the 0w group, hypocellularity and a slight decrease in safranin O stainability were observed around the injured area, but cartilage was restored to a nearly normal condition. In contrast, in the 1w and 2w groups, the cartilage surface was irregular and safranin O stainability in the injured and surrounding areas was poor. Histological score in the 0w group was significantly better than in the control, 1w, and 2w groups. At 1 day postinjection, fluorescent-labeled MSCs were mostly distributed in synovium. However, no migration into the PTCD was observed. Conclusions: Early intra-articular injection of MSCs was effective in enhancing cartilage healing in a rat PTCD model. Injected MSCs were distributed in synovium, not in cartilage surrounding the PTCD.